2018
DOI: 10.1002/jum.14556
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Brachial Plexus With Shear Wave Elastography After Radiotherapy for Breast Cancer

Abstract: Shear wave elastography showed that the brachial plexuses of patients receiving RT were stiffer than the unaffected brachial plexuses. Brachial plexus stiffening may be associated with fibrotic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
(22 reference statements)
0
15
0
1
Order By: Relevance
“…There have been limited studies on the use of ultrasound elastography to evaluate the brachial plexus . Ultrasound elastography is of potential interest in brachial plexus pathology as there are limitations of B‐mode ultrasound in this region.…”
Section: Resultsmentioning
confidence: 99%
“…There have been limited studies on the use of ultrasound elastography to evaluate the brachial plexus . Ultrasound elastography is of potential interest in brachial plexus pathology as there are limitations of B‐mode ultrasound in this region.…”
Section: Resultsmentioning
confidence: 99%
“…Shear wave elastography for assessing peripheral neuropathies has emerged in clinical practice and has shown that affected nerves have greater stiffness than those in healthy individuals . Shear wave elastography can display tissue stiffness in vivo, and we obtained 3 SWE parameters for displaying tissue stiffness: the shear modulus, elastic modulus, and SWS . Shear wave elastography is based on push pulse, high‐intensity US beams, which create an acoustic radiation force on the targeted tissue through the US probe .…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound (US) has been widely used for imaging peripheral neuropathy but has had unsatisfactory results . Shear wave elastography (SWE) is an advanced technique for displaying tissue elasticity by means of high‐frequency US waves in vivo and noninvasively . In recent studies, SWE showed promising results for displaying peripheral neuropathies in carpal tunnel syndrome, DM, Behçet disease, multiple sclerosis, and the brachial plexus .…”
mentioning
confidence: 99%
See 2 more Smart Citations